Estimation of the Water Requirements of Agricultural Crops in the Tajan River Basin, Sari - Maliheh Akbari; Mojtaba Farhadzadeh; Parisa Maleki (مهندسی و مدیریت ساخت)
Determining crop water requirements plays a crucial role in irrigation planning and, consequently, in the proper management of water resources in the agricultural sector. Therefore, this study examines the water consumption and requirements of agricultural crops in the Tajan River Basin, located in Mazandaran Province. The agricultural water needs and consumption within the study area include both net and gross crop water requirements. The net water requirement of field and orchard crops was estimated using data from the Plant Water Requirement Determination System of the Soil and Water Research Institute. Considering the irrigation efficiency for lands within the Tajan Plain, which fall under the Tajan irrigation network, as well as the upstream agricultural lands within the Tajan River Basin up to the plain's entrance (traditional irrigation system), the gross water requirement of each crop was estimated. The results of this study indicate that the net agricultural land area in the Tajan Plain is 68,100 hectares, with a projected water requirement of 433.5 million cubic meters. Additionally, the net agricultural land area in the Tajan River Basin up to the plain’s entrance is 15,300 hectares, with an estimated water requirement of 106 million cubic meters.